"Irony" of managing refractory anemia with transfusional support in hemophagocytic lymphohistiocytosis. Issue 1 (August 2016) - Lee, Sunyoung; Salehi, Ilnaz; Chary, Michael; Schiano, Thomas; Mascarenhas, John O.
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening derangement of the immune system in which host macrophages phagocytose the patient's own blood cells. Herein, we present the case of a patient with HLH and associated refractory anemia who developed rapid iron deposition in the liver after transfusion of sixteen units of packed red blood cells (RBCs). Before transfusion, neither a liver biopsy nor computed tomography scan demonstrated iron deposition in the organ parenchyma. After receiving sixteen units of packed RBCs, liver iron concentration rose to 6.7 mg/g dry weight, which is highly unusual in other diseases requiring transfusional support.